The Correlation of Salivary Gland Uptake Between 18F-FP-CIT PET/CT and Salivary Scan. (August 2020) - Kang, Seo Young; Yun, Ji Young; Kim, Hye Ok; Moon, Byung Seok; Yoon, Hai-Jeon; Kim, Bom Sahn
Abstract : Abstract: An 85-year-old woman visited our hospital with repetitive diarrhea, nausea, and anorexia, as well as aggressive behavior. The neurologist decided to perform dopamine transporter imaging ( 18 F-FP-CIT PET/CT) for accurate diagnosis, taking into account the potential adverse effects of L-dopa that the patient had been taking for a long time. The uptake of dopamine transporter in the bilateral basal ganglia was well preserved, but reduced uptake in the left parotid gland was incidentally detected. A subsequent salivary scan showed reduced uptake in the left parotid gland with the same pattern as that on 18 F-FP-CIT PET/CT.